2019
DOI: 10.1111/jnp.12185
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between social cognition and fatigue, depressive symptoms, and anxiety in multiple sclerosis

Abstract: Emerging research indicates that in addition to physical and cognitive deficits, individuals with multiple sclerosis (MS) may also have impairments in social cognition, such as facial affect recognition and Theory of Mind (ToM). However, there is little research into how social cognition impairments relate to other domains in MS, such as mood and fatigue levels. The current study investigated whether social cognitive ability is associated with fatigue, depressive symptoms and anxiety in MS. Twenty-eight indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 60 publications
(72 reference statements)
0
15
1
Order By: Relevance
“…In line with what we would expect, actual findings demonstrated the existence of these differences, supported by neuroimaging data even for SC competencies. Previous studies investigated ToM dysfunctions in the different courses of MS, and none of them identified any specific phenotype‐related patterns [41]. The actual study confirms MS patients' impairment in recognizing others' mental states, and highlights peculiar differences between RRMS and SPMS patients.…”
Section: Discussionmentioning
confidence: 61%
“…In line with what we would expect, actual findings demonstrated the existence of these differences, supported by neuroimaging data even for SC competencies. Previous studies investigated ToM dysfunctions in the different courses of MS, and none of them identified any specific phenotype‐related patterns [41]. The actual study confirms MS patients' impairment in recognizing others' mental states, and highlights peculiar differences between RRMS and SPMS patients.…”
Section: Discussionmentioning
confidence: 61%
“…Second, we only included cross-sectional studies, while more longitudinal studies are needed to investigate the dynamic changes in empathy and ToM function in patients of MS. Third, although we investigated some demographic and clinical variables (including age, sex, education level, disease duration, EDSS scores, severity of depression, and severity of anxiety) that may affect empathy and ToM function, other factors [such as prior substance abuse or some other behavioral symptoms (including apathy, inflexible, obsessive, sometimes with flattened affect, suspiciousness, etc.)] were not examined due to the limited data available in the original studies (67,113,114). Further studies are required to comprehensively elucidate the potential effects of these factors on empathy-and ToM-associated features in MS. Fifth, there was heterogeneity between the individual tasks for the assessment of ToM or empathy, and further development of standardized batteries for ToM/empathy assessment in MS is needed.…”
Section: Limitationsmentioning
confidence: 99%
“…As a result of this link between the high levels of IL-6 and the perception of anxiety, we can see that anxiety disorders are found amongst the most common psychiatric disorders associated with MS [13]. In addition, anxiety symptoms have an effect on the course of the disease, increasing the levels of fatigue [14] and especially functional disability [15].…”
Section: Introductionmentioning
confidence: 99%